The Social Construction of Space in an Urban Border of Rome Marginalization, Crime and Security Policies in Montespaccato - Martone, Vittorio; Cavallotti, Nicola (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
In the last few years, a complex and polycentric debate on marginal territories has taken shape, rekindling attention on the inner areas and the urban peripheries, where contradictions, inequalities and conflicts materialize, but where old and new forms of solidarity and social innovation are also activated and reactivated. This double essence shows only part of the complexity of these urban frontiers, which cannot be represented with a one single perspective. This essay aims at providing a contribution to this debate, examining the results of a case study carried out in a suburban area of Rome, observing two phenomena: the processes of marginalization, concentration of poverty, social disorganization, and political disaffection; the genesis of criminal phenomena, the urban security and law enforcement policies. The case study focuses on Montespaccato, in the north-west outskirts of the Capital. A borgata built at the beginning of the 1900s, during the urban expansion in the Roman countryside, which today has the characteristics of an urban frontier, an area with vague social boundaries, a lack of places of attraction and opportunities, as well as an urban configuration lacking compared to the needs of the inhabitants. In this scenario, recent judicial inquiries have shown the presence of organized crime groups, capable of territorial control executed through the threat but also the use of violence, leading to a subjugation of the local economy. To understand the coexistence of these phenomena, the case study aims at understanding the construction (or production) of territoriality in a Roman borgata in a social and historical key, meaning the territory as a constantly acted and (re) built process in its socio-cultural, political, economic, and ecological dimensions. Our thesis is that criminal phenomena must be situated in the historical process of transformation of the periphery and in the rupture of the community. Spontaneism, informality, disobedience and anti-politics have over time connoted the active periphery of the borgata making a “center on the edge”. The processes of modernization, individualization and secularization, the rupture of the community ties of provenance have fuelled the urban polarity by marginalizing the suburbs, reducing the spontaneous social control and the levers for regulating public life by the public and private institutions of the territory.